Kesan Perkongsian Pengetahuan Terhadap Tingkahlaku Kerja Inovatif, Penglibatan Pekerja Dan Prestasi Pekerja - ismail, fadillah (Research in Management of Technology and Business, 2022)
Knowledge sharing can enable organizations to gain an advantage in competition between the Malaysian furniture manufacturing industry, but the Malaysian furniture manufacturing industry is still considered a low-wage economy, this is due to lack of innovative work behaviors, employee engagement and employee performance and it has resulted in value and profit margin in the industry has decreased. The objective of this study was to determine the impact of knowledge sharing on innovative work behaviors, employee engagement, and performance among employees from the furniture manufacturing industry. Quantitative methods and stratified random sampling were used in this study to collect data of 173 employees from top and middle management in VS Concept Furniture Sdn Bhd, Fair Production Sdn Bhd and Poh Huat Furniture Industries (M) Sdn Bhd through online questionnaires, while descriptive analysis and inferential analysis were used to analyze the data. This study shows that there is a significant and positive relationship between knowledge sharing (knowledge donation and collecting) and innovative work behaviors (idea generation, idea promotion and idea realization), employee engagement (vigor, dedication, and absorption) and employee performance (task and contextual performance). Through the results of this study, researcher hope to help furniture manufacturing companies improve the overall knowledge of their employees by sharing knowledge and suggests that future researchers may get approval from companies to conduct walk-in questionnaire method by asking questions to respondents to get accurate data